Development and validation of a drinking water temperature model in domestic drinking water supply systems. Issue 10 (26th November 2017) - Zlatanovic, Ljiljana; Moerman, Andreas; van der Hoek, Jan Peter; Vreeburg, Jan; Blokker, Mirjam
Abstract: Domestic drinking water supply systems (DDWSs) are the final step in the delivery of drinking water to consumers. Temperature is one of the rate-controlling parameters for many chemical and microbiological processes and is, therefore, considered as a surrogate parameter for water quality processes. In this study, a mathematical model is presented that predicts temperature dynamics of the drinking water in DDWSs. A full-scale DDWS resembling a conventional system was built and run according to one year of stochastic demands with a time step of 10 s. The drinking water temperature was measured at each point-of-use in the systems and the data-set was used for model validation. The temperature model adequately reproduced the temperature profiles, both in cold and hot water lines, in the full-scale DDWS. The model showed that inlet water temperature and ambient temperature have a large effect on the water temperature in the DDWSs.